Glucose-6-phosphate Reduces Fosfomycin Activity Against Stenotrophomonas maltophilia - Gil-Gil, Teresa; Martínez, José Luis (Frontiers in Microbiology, 2022)
It is generally accepted that fosfomycin activity is higher in the presence of glucose-6-phosphate, since its inducible transporter UhpT is one of the gates for fosfomycin entry. Accordingly, fosfomycin susceptibility tests are performed in the presence of this sugar; however, since Stenotrophomonas maltophilia lacks UhpT, it is doubtful that glucose-6-phosphate might be a fosfomycin adjuvant in this microorganism. The aim of the work is to determine if glucose-6-phosphate or other metabolites may alter the activity of fosfomycin against S. maltophilia. To that goal, checkerboard assays were performed to analyse synergy and antagonism of compounds such as glucose-6-phosphate, fructose, phosphoenolpyruvate or glyceraldehyde-3-phosphate, among others, with fosfomycin. Besides, minimal inhibitory concentrations of fosfomycin against a set of clinical S. maltophilia isolates presenting different levels of expression of SmeDEF efflux pump were determined in the presence and absence of said compounds. Finally, intracellular fosfomycin concentrations were determined using a bioassay. Our results show that, opposite to what has been described for other bacteria, glucose-6-phosphate does not increase fosfomycin activity against S. maltophilia; it is a fosfomycin antagonist. However, other metabolites as fructose, phosphoenolpyruvate and glyceraldehye-3-phosphate increase fosfomycin activity. Consistent with these results, glucose-6-phosphate decreases fosfomycin internalization (a feature against current ideas in the field), while the other three compounds increase the intracellular concentration of this antibiotic. These results support that current standard fosfomycin susceptibility tests made in the presence of glucose-6-phosphate do not account for the actual susceptibility to this antibiotic of bacteria such as S. maltophilia. Finally, the innocuous metabolites that increase S. maltophilia susceptibility to fosfomycin found in this work are potential adjuvants, which might be included in fosfomycin formulations used for treating infections by this resistant pathogen.